Harnessing performance through digital technology adoption: An empirical analysis of SMEs in the Tanzanian fruit juice processing industry - Utonga, Dickson; Tundui, Charles Stephen; Mkuna, Eliaza (Taylor and Francis ( Cogent Business & Management), 2026)
Paper submitted to the Journal Cogent Business & Management